An organ of murder: crime, violence, and phrenology in nineteenth-century America - Thompson, Courtney E. (Critical issues in health and medicine, 2021)
"An Organ of Murder explores the origins of both popular and elite theories of criminality in the nineteenth-century United States, focusing in particular on the influence of phrenology. In the United States, phrenology shaped the production of medico-legal knowledge around crime, the treatment of the criminal within prisons and in public discourse, and sociocultural expectations about the causes of crime. The criminal was phrenology's ideal research and demonstration subject, and the courtroom and the prison were essential spaces for the staging of scientific expertise. In particular, phrenology constructed ways of looking as well as a language for identifying, understanding, and analyzing criminals and their actions. This work traces the long-lasting influence of phrenological visual culture and language in American culture, law, and medicine, as well as the practical uses of phrenology in courts, prisons, and daily life"--